A new Hyphessobrycon (Ostariophysi: Characiformes: Characidae) from the middle Amazon basin, Brazil - Lima, Flávio C.t.; Coutinho, Daniel P.; Wosiacki, Wolmar B. (Zootaxa, 2014)
Hyphessobrycon montagi, new species, is described from tributaries of the Rio Arapiuns, a left margin affluent of the lower Rio Tapajós, Amazon basin, Pará, Brazil. The new species can be diagnosed from all its congeners by the possession of a combination of two well-defined humeral blotches, connected by a narrow stripe, and a caudal peduncle blotch. A putatively monophyletic Hyphessobrycon heterorhabdus species-group, restricted to H. heterorhabdus, H. amapaensis, and H. eschwartzae, is herein proposed based on shared derived features of color pattern. Alternative proposals of a “Hyphessobrycon heterorhabdus group” presented in the recent literature are evaluated and criticized.